Implementation Framework for Millennial and Generation Z Employee Retention Strategy: An Operational Model for Indonesian State Owned Banking Enterprises - Rusmewahni; Darmilisani; Siti Kadariah; Vina Winda Sari (Fundamental and Applied Management Journal, 2026)
Retaining young employees has become an increasingly important human resource issue for Indonesian State-Owned Enterprises, particularly as Millennials and Generation Z now represent a substantial proportion of the workforce. These generations often bring different expectations regarding meaningful work, career growth, workplace flexibility, recognition, supportive leadership, and organizational care. Traditional retention approaches that emphasize job security, compensation, and seniority-based loyalty are no longer sufficient to address these changing expectations. This study aims to design and evaluate an operational framework for improving the retention of Millennial and Generation Z employees in state-owned banking service enterprises in North Sumatra, Indonesia. A Research and Development design was applied using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected from 250 actual employee respondents, 15 interview informants, five expert validators, and a pre-implementation and post-implementation evaluation process. Quantitative data were analyzed using descriptive statistics, validity and reliability testing, correlation analysis, multiple regression analysis, and paired-sample comparison. Qualitative data were examined through thematic analysis. The results indicate that organizational commitment, job satisfaction, career development, and recognition are the strongest factors associated with lower turnover intention and stronger intention to stay. The final framework consists of seven components: organizational support, career development, supportive leadership, work-life balance, rewards and recognition, adaptive work environment, and employee engagement. Expert validation confirmed that the framework was relevant, feasible, measurable, and suitable for the characteristics of younger employees. The evaluation results showed improvements in several retention-supporting conditions and a decrease in turnover intention after implementation. However, because the study did not use a control group, the findings should be interpreted as indicative evidence rather than definitive causal proof. This study provides a practical and measurable operational model for strengthening young employee retention in state-owned banking service enterprises.